Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Let's solve the system of linear equations given:
1) [tex]\( 5x + 3y = 21 \)[/tex]
2) [tex]\( -2x + 4y = 2 \)[/tex]
We will solve this system using the method of substitution or elimination.
### Step-by-Step Solution:
#### Step 1: Set up the equations in matrix form
We can represent the system of linear equations with a coefficient matrix [tex]\( A \)[/tex] and a constant matrix [tex]\( B \)[/tex]:
[tex]\[ A \cdot \begin{pmatrix} x \\ y \end{pmatrix} = B \][/tex]
Where [tex]\( A = \begin{pmatrix} 5 & 3 \\ -2 & 4 \end{pmatrix} \)[/tex] and [tex]\( B = \begin{pmatrix} 21 \\ 2 \end{pmatrix} \)[/tex].
#### Step 2: Use substitution or elimination method
Using elimination:
1. Multiply Equation 1 by 2 to make the coefficients of [tex]\(x\)[/tex] in both equations equal:
[tex]\[ 2 \cdot (5x + 3y) = 2 \cdot 21 \][/tex]
This yields:
[tex]\[ 10x + 6y = 42 \quad \text{(Equation 3)} \][/tex]
2. Add Equation 2 to Equation 3:
[tex]\[ (10x + 6y) + (-2x + 4y) = 42 + 2 \][/tex]
Simplifying this, we get:
[tex]\[ (10x - 2x) + (6y + 4y) = 44 \][/tex]
Which simplifies to:
[tex]\[ 8x + 10y = 44 \quad \text{(Equation 4)} \][/tex]
3. Now solve Equation 4 for [tex]\( y \)[/tex]:
[tex]\[ 8x + 10y = 44 \][/tex]
Notice there might have been a likely approach mistake, instead, we normalize the equation first if needed. We can combine the coefficients accordingly instead.
Combine coefficients properly:
- Equation after normalization from the 4th:
Multiply Equation 2 by 5:
[tex]\[ 5 \cdot (-2x + 4y) = 5 \cdot 2 \][/tex]
Yielding:
[tex]\[ - 10x + 20y = 10 \quad (Equation 5) \][/tex]
Add results of valid Equation3 and Equation5:
10x+6y+(-10x+20y)=42+10
Simplifies to
26 y = 52
Recovered fast approach back. Valid substitution indeed says:
[tex]\[ y= 2 \][/tex]
#### Step 3: Solve for [tex]\(x\)[/tex]:
Using [tex]\(y=2\)[/tex] in first simpler equation
we combine coefficients as:
[tex]\[ 5x + 3(2)=21\][/tex]
Solving:
5x +6=21
\]
So
\[
5x=15
obtaining result:
\[.
Thus the results through good solving steps, recover accurate results:
\boxed{ x = 3, y=2 }
Thus:
\boxed{(3,2)}
1) [tex]\( 5x + 3y = 21 \)[/tex]
2) [tex]\( -2x + 4y = 2 \)[/tex]
We will solve this system using the method of substitution or elimination.
### Step-by-Step Solution:
#### Step 1: Set up the equations in matrix form
We can represent the system of linear equations with a coefficient matrix [tex]\( A \)[/tex] and a constant matrix [tex]\( B \)[/tex]:
[tex]\[ A \cdot \begin{pmatrix} x \\ y \end{pmatrix} = B \][/tex]
Where [tex]\( A = \begin{pmatrix} 5 & 3 \\ -2 & 4 \end{pmatrix} \)[/tex] and [tex]\( B = \begin{pmatrix} 21 \\ 2 \end{pmatrix} \)[/tex].
#### Step 2: Use substitution or elimination method
Using elimination:
1. Multiply Equation 1 by 2 to make the coefficients of [tex]\(x\)[/tex] in both equations equal:
[tex]\[ 2 \cdot (5x + 3y) = 2 \cdot 21 \][/tex]
This yields:
[tex]\[ 10x + 6y = 42 \quad \text{(Equation 3)} \][/tex]
2. Add Equation 2 to Equation 3:
[tex]\[ (10x + 6y) + (-2x + 4y) = 42 + 2 \][/tex]
Simplifying this, we get:
[tex]\[ (10x - 2x) + (6y + 4y) = 44 \][/tex]
Which simplifies to:
[tex]\[ 8x + 10y = 44 \quad \text{(Equation 4)} \][/tex]
3. Now solve Equation 4 for [tex]\( y \)[/tex]:
[tex]\[ 8x + 10y = 44 \][/tex]
Notice there might have been a likely approach mistake, instead, we normalize the equation first if needed. We can combine the coefficients accordingly instead.
Combine coefficients properly:
- Equation after normalization from the 4th:
Multiply Equation 2 by 5:
[tex]\[ 5 \cdot (-2x + 4y) = 5 \cdot 2 \][/tex]
Yielding:
[tex]\[ - 10x + 20y = 10 \quad (Equation 5) \][/tex]
Add results of valid Equation3 and Equation5:
10x+6y+(-10x+20y)=42+10
Simplifies to
26 y = 52
Recovered fast approach back. Valid substitution indeed says:
[tex]\[ y= 2 \][/tex]
#### Step 3: Solve for [tex]\(x\)[/tex]:
Using [tex]\(y=2\)[/tex] in first simpler equation
we combine coefficients as:
[tex]\[ 5x + 3(2)=21\][/tex]
Solving:
5x +6=21
\]
So
\[
5x=15
obtaining result:
\[.
Thus the results through good solving steps, recover accurate results:
\boxed{ x = 3, y=2 }
Thus:
\boxed{(3,2)}
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.